Cotyledons facilitate the adaptation of early‐maturing soybean varieties to high‐latitude long‐day environments. (6th June 2021) - Xu, Xin; Zhang, Lixin; Cao, Xiaoning; Liu, Lifeng; Jiang, Bingjun; Zhang, Chunlei; Jia, Hongchang; Lyu, Xiangguang; Su, Yumei; Cai, Yupeng; Liu, Luping; Zhang, Shengrui; et al.
Abstract: Soybean ( Glycine max ), a typical short‐day plant (SDP) domesticated in temperate regions, has expanded to high latitudes where daylengths are long from soybean emergence to bloom, but rapidly decrease from seed filling to maturity. Cotyledons are well known as the major storage organs in seeds, but it is unclear whether developing cotyledons store flowering substances at filling stage in SD for upcoming seedlings, or instead respond to photoperiod for floral induction after emergence of matured seeds in long‐day (LD). Here, we report that cotyledons accelerate flowering of early‐maturing varieties not resulting from stored floral stimuli but by perceiving photoperiod after emergence. We found that light signal is indispensable to activate cotyledons for floral induction, and flowering promoting gene GmFT2a is required for cotyledon‐dependent floral induction via upregulation of floral identity gene GmAP1 . Interestingly, cotyledons are competent to support the entire life cycle of a cotyledon‐only plant to produce seeds, underlying a new photoperiod study system in soybean and other dicots. Taken together, these results demonstrate a substantial role for cotyledons in flowering process, whereby we propose a 'cotyledon‐based self‐reliance' model highlighting floral induction from emergence as a key ecological adaptation for rapid flowering of SDPs grown in LD environments at high latitudes. Abstract : The cotyledons induce soybean flowering by expressing flowering promoting gene GmFT2a after perceiving light signals at seedling stage. The cotyledon‐dependent floral induction accelerates the flowering of early‐maturing varieties in long‐day and facilitate them adapting to high latitudes.